2009
DOI: 10.1016/j.expneurol.2009.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of adrenoreceptors inhibits the splenic response to stroke

Abstract: Recent studies have highlighted the involvement of the peripheral immune system in delayed cellular degeneration after stroke. In the permanent middle cerebral artery occlusion (MCAO) model of stroke, the spleen decreases in size. This reduction occurs through the release of splenic immune cells. Systemic treatment with human umbilical cord blood cells (HUCBC) 24 hours post-stroke blocks the reduction in spleen size while significantly reducing infarct volume. Splenectomy two weeks prior to MCAO also reduces i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 49 publications
(53 reference statements)
4
122
2
4
Order By: Relevance
“…Separate experiments completed by Offner et al have shown a peripheral increase in production of the pro inflammatory cytokines TNF , IFN , IL-6, MCP-1, and IL-2 after ischemic stroke . Further work completed by Ajmo et al has shown that ischemic stroke is associated with adrenergic output that stimulates the spleen to release immune (T and B cells) into the systemic circulation that ultimately lead to increased cavity size after MCAO stroke in a rodent model (Ajmo, et al, 2009). Furthermore, Verdrame et al have shown similar results indicating the release of immune cells (CD8+ T cells) is correlated with a reduction in splenic mass.…”
Section: Discussionmentioning
confidence: 99%
“…Separate experiments completed by Offner et al have shown a peripheral increase in production of the pro inflammatory cytokines TNF , IFN , IL-6, MCP-1, and IL-2 after ischemic stroke . Further work completed by Ajmo et al has shown that ischemic stroke is associated with adrenergic output that stimulates the spleen to release immune (T and B cells) into the systemic circulation that ultimately lead to increased cavity size after MCAO stroke in a rodent model (Ajmo, et al, 2009). Furthermore, Verdrame et al have shown similar results indicating the release of immune cells (CD8+ T cells) is correlated with a reduction in splenic mass.…”
Section: Discussionmentioning
confidence: 99%
“…By these molecules, infiltrating neutrophils amplify a cerebral inflammatory response that may exacerbate post-ischemic brain damage (49,51,52). Furthermore, infiltrating neutrophils are the primary source of enhanced matrix metalloproteinase 9 activity in the ischemic brain, which is a critical mechanism underlying the breakdown of the BBB and the exacerbation of neurological injury (53).…”
Section: Microglia-innate Immune Cells Of the Brainmentioning
confidence: 99%
“…14 It has further been demonstrated in experimental stroke models that pre or immediate poststroke surgical removal or irradiation of the spleen attenuates these responses, and results in reduced stroke lesion size and enhanced recovery. 5,[14][15][16][17][18][19] The pre-clinical body of evidence raises an exciting possibility that novel therapies can be designed to target the spleen as an approach to modulate post-stroke inflammation and dampen secondary brain injury. [20][21][22][23][24] However, the road to translation of these findings in the clinical setting is beset with challenges.…”
Section: Introductionmentioning
confidence: 99%